1985
DOI: 10.1161/01.cir.72.6.1244
|View full text |Cite
|
Sign up to set email alerts
|

Survival and functional results after valve replacement for aortic regurgitation from 1976 to 1983: impact of preoperative left ventricular function.

Abstract: Our results indicate that preoperative left ventricular systolic function continues to influence postoperative prognosis and suggest that the discordant conclusions of previous studies probably resulted from interpretive differences and differences in patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
4

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(69 citation statements)
references
References 50 publications
2
62
1
4
Order By: Relevance
“…The usual operative mortality rate reported for AVR ranges from 1% to 7%. 4,7,8,15 Our study undeniably shows excessive operative mortality rates among patients with markedly low EF, but it is not overwhelming, particularly for patients not requiring associated procedures (7.7%). Most importantly, our data indicate that a majority of patients remain free of heart failure 10 years after AVR.…”
Section: Ar and Markedly Reduced Ef: Outcome Implicationsmentioning
confidence: 65%
See 3 more Smart Citations
“…The usual operative mortality rate reported for AVR ranges from 1% to 7%. 4,7,8,15 Our study undeniably shows excessive operative mortality rates among patients with markedly low EF, but it is not overwhelming, particularly for patients not requiring associated procedures (7.7%). Most importantly, our data indicate that a majority of patients remain free of heart failure 10 years after AVR.…”
Section: Ar and Markedly Reduced Ef: Outcome Implicationsmentioning
confidence: 65%
“…6 The very definition of thresholds for defining a marked reduction of left ventricular (LV) function in patients with severe AR is unknown, and little is known about the outcome of patients with such severe reduction because previous studies included few patients with markedly reduced EF. 5,7,8 It is unclear how to identify a high-risk group in the setting of severe AR, thus making the treatment and outcome of such patients unclear. For these patients, uncertainty remains regarding treatment options and whether to recommend vasodilator therapy or cardiac transplantation rather than AVR and recent guidelines underscore the need for new data on long-term outcome.…”
Section: See P 2637mentioning
confidence: 99%
See 2 more Smart Citations
“…This can progress to the extent that the full benefit of surgical correction of the regurgitant lesion, in terms of recovery of LV function and improved survival, can no longer be achieved. 244,[247][248][249][250][251][252][253][254][255][256] A large number of studies have identified LV systolic function and end-systolic size as the most important determinants of survival and postoperative LV function in patients undergoing AVR for chronic AR. 235, Studies of predictors of surgical outcome are listed in Table 13.…”
Section: Pathophysiologymentioning
confidence: 99%